2012
DOI: 10.1590/s0102-86502012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Filling of extraction sockets with autogenous bone in cats

Abstract: PURPOSE: To evaluate bone healing in the extraction socket of the feline mandibular canine tooth after grafting. METHODS: Eighteen adult cats were submitted to unilateral extraction of mandibular canine tooth and divided into three groups. In group 1 (n=6), control, the extraction socket was left empty. In group 2 (n=6), the extraction socket was filled with autogenous cancelous bone from the iliac crest and in group 3 (n=6), with cortical bone chips from the iliac crest. Cats were euthanized at 6 weeks postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Intraoral radiology provided better results than the extraoral radiographic technique which was used in another experiment in cats 8 . But probably, the best images of extraction wounds are obtained with microcomputed tomography scan, as demonstrated by Kumarswamy et al Mean values somewhat lower, around 50%, were observed in the histometric examinations of another experiment performed on cats, with an observation period of six weeks, in which the extraction sockets of mandibular canine teeth were filled with autogenous cancellous bone or cortical bone chips 8 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Intraoral radiology provided better results than the extraoral radiographic technique which was used in another experiment in cats 8 . But probably, the best images of extraction wounds are obtained with microcomputed tomography scan, as demonstrated by Kumarswamy et al Mean values somewhat lower, around 50%, were observed in the histometric examinations of another experiment performed on cats, with an observation period of six weeks, in which the extraction sockets of mandibular canine teeth were filled with autogenous cancellous bone or cortical bone chips 8 .…”
Section: Discussionmentioning
confidence: 94%
“…The use of a variety of materials to fill extraction sockets has been studied in order to accelerate bone regeneration, maintain alveolar ridge and reinforce the resistance of the maxilla or mandible [1][2][3][4][5][6][7][8] . Some of the more common indications for extraction of teeth in cats include crown fracture with pulp exposure, periodontal disease, feline odontoclastic resorptive lesions and feline chronic gingivostomatitis [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…9 Autogenous bone (cancellous bone and cortical bone chips) as well as allograft- based (demineralized bone of the same species) and ceramic-based (calcium phosphate, calcium sulfate and bioglass) bone graft substitutes are most commonly used in veterinary dentistry, although they are not routinely needed in extraction sites. 12,13 Gauze swabs (size 3 x 3 inches, 7.5 x 7.5 cm) allow digital control of hemorrhage during tooth extraction procedures. Lavage with refrigerated lactated Ringer ‘s solution may also provide good hemostasis.…”
Section: Equipment Instruments and Materials For Tooth Extractionmentioning
confidence: 99%
“…6,7,9,10,13 The general goals of the treatment are reestablishing bone continuity, obtaining appropriate dental occlusion, and restoring functional aspects. 2,6,15,16 Bone plates and screws are the most frequent alloplastic implants used for mandibular reconstruction. 3,6,[8][9][10]16 In general, reconstruction plates are rigid implants used on the ventral aspect of the mandible in order to stabilize the remaining segments to preserve the facial contour and occlusion as well as to stabilize bone grafts in a suitable position when used.…”
Section: Introductionmentioning
confidence: 99%